2015
DOI: 10.1002/2014jb011572
|View full text |Cite
|
Sign up to set email alerts
|

Stacking global GPS verticals and horizontals to solve for the fortnightly and monthly body tides: Implications for mantle anelasticity

Abstract: The availability of long-term position measurements from permanent GPS stations distributed around the Earth makes it feasible to extract small, globally coherent, long-period geophysical signals from the data. Using 11 years of daily vertical and horizontal positions from over 600 permanent GPS stations worldwide, we solve for the amplitude and phase of the fortnightly and monthly body tides by stacking the surface displacements against spherical harmonics and isolating the fortnightly and monthly signals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 44 publications
1
32
2
Order By: Relevance
“…Applying the classical α-law over the seismic to tide frequency band, Benjamin et al (2006), Kang et al (2015), and Ray and Egbert (2012) showed that anelasticity has an impact on the geoid (body tide), and a value of α in the range of 0.15-0.30 can fit geodetic observations reasonably well. Different from the traditional normal mode (TNM) theory used to study body tides, Benjamin et al (2006), Lau et al (2015), and Wahr and Bergen (1986) developed an extended normal mode (ENM) approach, which predicts a more accurate perturbation of body tides due to anelasticity (Lau et al, 2016).…”
mentioning
confidence: 99%
“…Applying the classical α-law over the seismic to tide frequency band, Benjamin et al (2006), Kang et al (2015), and Ray and Egbert (2012) showed that anelasticity has an impact on the geoid (body tide), and a value of α in the range of 0.15-0.30 can fit geodetic observations reasonably well. Different from the traditional normal mode (TNM) theory used to study body tides, Benjamin et al (2006), Lau et al (2015), and Wahr and Bergen (1986) developed an extended normal mode (ENM) approach, which predicts a more accurate perturbation of body tides due to anelasticity (Lau et al, 2016).…”
mentioning
confidence: 99%
“…From Table 1, we can find that our estimates have certain (not too large) deviations from the values suggested by IERS Convention 2010. When comparing our estimates for the Mm and Mf with those of Krásná et al (2013) and Kang et al (2015), we can find that Krásná et al (2013)'s results have large deviations from our and Kang et al (2015)'s results (and the IERS reference values), and their imaginary parts h I and l I are even positive values (marked by gray areas in Table 1). As for the estimation errors of the Mf and Mm tides, our results are generally less than those of Kang et al (2015).…”
Section: Results For the Love Number L 20mentioning
confidence: 57%
“…This bootstrap procedure has been widely used for uncertainty estimations in various geophysical studies (e.g., Chen et al, 2013;Ding & Chao, 2015;Häfner & Widmer-Schnidrig, 2013;Widmer, et al, 1992). Kang et al (2015) further considered the errors of the ocean load tide model and the load Green's function. Compared with the uncertainties estimated from the real data based on the bootstrap procedure, such errors are too small and hence we ignore them in this study.…”
Section: Results For the Love Number L 20mentioning
confidence: 99%
See 1 more Smart Citation
“…While exhibiting the spatial variability necessary for sensitivity to Earth's rheology at the appropriate depths, such observations are therefore too short in period to impinge directly on the question of postseismic deformation in the Earth's lower crust or asthenosphere. In contrast, the Earth's body tides, which likewise show evidence of lower mantle anelasticity at semidiurnal right through to decadal timescales (Benjamin et al, ; Kang et al, ), are large‐scale phenomena and are therefore largely insensitive to the rheology of the outermost few hundred kilometers of the Earth.…”
mentioning
confidence: 99%